Immobilization of modular peptides on graphene cocktail for differentiation of human mesenchymal stem cells to hepatic-like cells - Adibi-Motlagh, Behzad; Hashemi, Ehsan; Akhavan, Omid; Khezri, Jafar; Rezaei, Aram; Zamani Amir Zakria, Javad; Siadat, Seyed Davar; Sahebghadam Lotfi, Abbas; Farmany, Abbas (Frontiers in Chemistry, 2022)
In this paper, two novel biomimetic modular peptide motifs based on alpha-2 subunit of type IV collagen (CO4A2) were designed and immobilized on a graphene platform to imitate integrin and heparan sulfate (HS)-binding proteins. The in silico study was used to design 9-mer K[KGDRGD]AG and 10-mer KK[SGDRGD]AG for testing designed Integrin-Binding Peptide (dIBP) and HS-Binding Peptide (dHBP). Virtual docking technique was used to optimize the peptide motifs and their relevant receptors. Molecular dynamic (MD) simulation was used to evaluate the stability of peptide-receptor complexes. The effect of platform on human mesenchymal stem cells (hMSCs) differentiation to hepatic-like cells (HLCs) was evaluated. After differentiation, some hepatic cells molecular markers such as Albumin, AFP, CK-18 and CK-19 were successfully followed. It was shown that graphene-heparan sulfate binding peptide (G-HSBP) enhances the mature hepatic markers expression instead of control (p≤0.05). Pathological study showed that the designed platform is safe and no adverse effect was seen till 21 days after implantation.